PENERAPAN METODE STAD UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BAHASA INGGRIS DI KELAS XI IPA. 3 SMA NEGERI 1 BANDAR BARU - Mardiana Mardiana (Universitas Jabal Ghafur, 2020)
This study aims to determine the increase in learning motivation which will ultimately improve student learning outcomes in learning English Class XI Science. 3 by implementing the STAD (Student Team Achievement Division) cooperative learning in SMA 1 Bandar Baru, the second semester of the 2013/2014 school year. This type of research includes action research. The subjects of this study were students of Class XI Science. 3 in SMA Negeri 1 Bandar Baru. The results of this study indicate: Through the results of classroom action research at Bandar Baru 1 High School there was an increase in learning motivation, namely in the first cycle the average was 65.77 while in the second cycle it was 80.38. Before learning is done with the STAD Method (Student Team Achievement Division) the student score is 61.35. In the first cycle the results of student evaluations on English subjects get an average score of 68.85, meanwhile, student learning activities and teacher performance obtain a value of 64.80% and 62.50% while in the second cycle get an average score of 77 , 31. From the study there was an increase in learning completeness as much as in the first cycle of 46% and in the second cycle was 88%. Student learning activities increased to 73.00%, while teacher performance increased to 87.50 Thus, it can be concluded that the implementation of classroom action research through the STAD (Student Team Achievement Division) cooperative learning method for learning English in order to increase learning motivation with itself can improve learning outcomes for students of Class XI Science. 3 SMA Negeri 1 Bandar Baru. Keywords: STAD Cooperative Learning Method (Student Team Achievement Division) Results of Learning English